Time in the Triple Helix: A Foundation for Innovation - Winsor, Blair; Hall, Heather (Journal of Management Policy and Practice, 2018)
There has been considerable work investigating how the ‘triple helix’ enhances firm-level innovation. The contention is that innovation results from helix participants’ activities. However, little attention is paid to the potential for the participants’ different temporal frameworks to disrupt innovation. Understanding time in helix activity is therefore important. We describe how participants were able to adapt their temporal frameworks and build ‘helix time’, based on qualitative data from three helix projects. We theorise that key to building the temporal consensus of helix time is a preparedness to share temporal conceptions and individuals/or institutions capable of temporal boundary spanning.